2012
DOI: 10.1016/j.ejogrb.2012.07.014
|View full text |Cite
|
Sign up to set email alerts
|

GnRH agonist versus GnRH antagonist in IVF/ICSI cycles with recombinant LH supplementation: DNA fragmentation and apoptosis in granulosa cells

Abstract: The results suggest that therapy with either an agonist or antagonist of GnRH is associated with comparable levels of DNA fragmentation and apoptosis in granulosa cells in ICSI cycles supplemented with rLH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 20 publications
1
7
0
3
Order By: Relevance
“…Conversely, FF cfDNA content did not differ according to the type of COS protocols (agonist versus antagonist). In agreement, similar apoptosis levels were detected in granulosa cells exposed to agonist or antagonist treatments [ 43 ].…”
Section: Discussionsupporting
confidence: 79%
“…Conversely, FF cfDNA content did not differ according to the type of COS protocols (agonist versus antagonist). In agreement, similar apoptosis levels were detected in granulosa cells exposed to agonist or antagonist treatments [ 43 ].…”
Section: Discussionsupporting
confidence: 79%
“…GnRH-a protocol [23-27]: The pituitary downregulation began during the luteal phase of the previous menstrual cycle with the GnRH-a leuprolide acetate (leuprolide acetate; Lupron®; Abbott, Brazil) at a dose of 1 mg/day for 14 days. The ovaries were then stimulated with a fixed dose of 150–225 IU of recombinant FSH (rFSH; Gonal F®; Serono, Brazil) and 75 IU/day of recombinant luteinising hormone (rLH; Luveris®; Serono, Brazil) for a period of 7 days.…”
Section: Methodsmentioning
confidence: 99%
“…GnRH-ant protocol [23-27]: On day 3 of the cycle, ovarian stimulation was induced with a fixed dose of 150–225 IU of rFSH and 75 IU/day of rLH for a period of 5 days. The decision on the starting dose of FSH was based on patient’s age.…”
Section: Methodsmentioning
confidence: 99%
“…32 The GnRH agonist, on the other hand, is administered for a longer duration throughout the cycle, competitively blocking the ovarian FSH receptors and suppressing the ovarian response to the gonadotropins. 33 However, most of the studies have not found any difference in response to either protocols. 8,22,30,34 Several studies found that the total duration of stimulation and total dosage of gonadotropins in the antagonist group was much less than that in long agonist group.…”
Section: Discussionmentioning
confidence: 96%